2008
DOI: 10.1063/1.2837028
|View full text |Cite
|
Sign up to set email alerts
|

Electron capture and emission properties of interface states in thermally oxidized and NO-annealed SiO2/4H-SiC

Abstract: Postoxidation annealing in nitric oxide ͑NO͒ results in a significant reduction of electronic states at SiO 2 / 4H-SiC interfaces. Measurements of electron trapping dynamics at interface states in both thermally oxidized and NO annealed SiO 2 / 4H-SiC interfaces were performed using constant-capacitance deep level transient spectroscopy ͑CCDLTS͒ and double-CCDLTS. We show that the interface state density in as-oxidized samples consists of overlapping distributions of electron traps that have distinctly differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 21 publications
3
15
0
Order By: Relevance
“…This trend is not specific to the NI states and is also observed for other interface states. 12,[20][21][22] The capture cross section of the NI states is larger than that of the other interface states, even near the E C . At E C ÀE T ¼ 0.15 eV, for example, the capture cross section of the NI states is about 1 Â 10 À14 cm 2 , while that of the conventional interface states is 10 À20 -10 À18 cm 2 .…”
Section: Resultsmentioning
confidence: 96%
“…This trend is not specific to the NI states and is also observed for other interface states. 12,[20][21][22] The capture cross section of the NI states is larger than that of the other interface states, even near the E C . At E C ÀE T ¼ 0.15 eV, for example, the capture cross section of the NI states is about 1 Â 10 À14 cm 2 , while that of the conventional interface states is 10 À20 -10 À18 cm 2 .…”
Section: Resultsmentioning
confidence: 96%
“…Since SiC is a compound material of Si and C atoms, that is why the role of C atoms during the thermal growth of SiO 2 has been observed to be very crucial. Several studies [7][8][9] confirm the presence of C species in the thermally grown oxide, which directly affect the interface as well as dielectric properties of metal-oxide-semiconductor structures [10]. For this reason, rigorous studies on electrical behavior of thermally grown SiO 2 on SiC play a fundamental role in the understanding and control of electrical characteristics of SiCbased devices.…”
Section: Introductionmentioning
confidence: 99%
“…The observed slow interface traps cannot be explained solely by the fast interface states that reside exactly at the interface, and it is necessary to take the existence of NITs into account [14,19]. It has also been shown that the electron capture cross-section of the interface traps varies by several orders of magnitude and the value is small near the conduction band edge [26,27]. This implies that the traps are located in the oxide near the interface, and the capture cross-section is small because of the distance from the interface.…”
Section: Discussionmentioning
confidence: 99%